Nucleic acid aptamers in therapeutic anticoagulation - Becker, Richard C.; Rusconi, Christopher; Sullenger, Bruce (Thrombosis and Haemostasis, 2005)
The evolution of anticoagulant therapy for the prevention and treatment of thrombotic disorders has progressed at a relatively modest pace considering the scope of the problem and our current understanding of platelet biology, coagulation proteases, and vascular science as they apply to protective haemostasis and pathologic thrombosis. Recent observations, dedicated to cellular-based models of coagulation, provide fundamental constructs, mechanistic clarity, and potentially unparalleled opportunity for accelerating the development and wide-scale clinical use of safe, effective, regulatable and patient-specific therapies. The following review introduces a novel domain of anticoagulant therapy referred to as aptamers (derived from the Latin aptus – to fit), considering their history, development, and potential application in patient care arenas.
Keywords: Aptamers; protein-binding oligonucleotides; anticoagulant therapy